2008 European Conference on Radiation and Its Effects on Components and Systems 2008
DOI: 10.1109/radecs.2008.5782711
|View full text |Cite
|
Sign up to set email alerts
|

Transient response of 3-D Multi-Channel nanowire MOSFETs submitted to heavy ion irradiation: A 3-D simulation study

Abstract: The response to single-event of 3-D Multi-Channel nanowire MOSFETs is investigated by 3-D numerical simulation. Drain current transient and charge collection are analyzed as function of the ion strike location, direction and track radius.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In [3] and [4] 3-D TCAD simulations were employed to model the response to radiation of FinFETs. In addition, Munteanu et al [5] demonstrated that 3T-FinFET and 3T-Multi-channel nanowires have better radiation hardness than conventional fullydepleted single-gate SOI transistors. In [6], alpha-particle and cosmic ray induced SER benefits of 22 nm high-K and metalgate bulk Tri-Gate devices have been measured and compared against equivalent devices manufactured in a 32 nm planar bulk CMOS technology.…”
Section: Introductionmentioning
confidence: 99%
“…In [3] and [4] 3-D TCAD simulations were employed to model the response to radiation of FinFETs. In addition, Munteanu et al [5] demonstrated that 3T-FinFET and 3T-Multi-channel nanowires have better radiation hardness than conventional fullydepleted single-gate SOI transistors. In [6], alpha-particle and cosmic ray induced SER benefits of 22 nm high-K and metalgate bulk Tri-Gate devices have been measured and compared against equivalent devices manufactured in a 32 nm planar bulk CMOS technology.…”
Section: Introductionmentioning
confidence: 99%